FAKTOR-FAKTOR PENENTU NILAI PERUSAHAAN: ANALISIS PERAN LEVERAGE, PROFITABILITAS, DAN PERTUMBUHAN PERUSAHAAN - Agus Riyanto; Erni Setiawati; Siti Rohmah; Pilipus Pilipus; Karina Kalpiani (OBOR: Oikonomia Borneo, 2026)
This study aims to analyze and test the real influence of several independent factors, namely Leverage (X1), Profitability (X2), and Company Growth (X3), on Company Value (Y). This study was conducted on manufacturing companies in the basic and chemical industry sectors listed on the Indonesia Stock Exchange (IDX) for three years, namely the period 2021 to 2023. To measure Company Value, the Price to Book Value (PBV) ratio was used, Leverage was measured by the Debt to Equity Ratio (DER), and Profitability was measured by Return on Equity (ROE). This study is causal and uses a quantitative approach. To select the sample, a purposive sampling technique was used, resulting in 18 companies as samples with a total of 54 observation data over three years. The analytical methods used were Multiple Linear Regression and Classical Assumption Test. Theoretically, this study is supported by three theories, namely Agency Theory, Pecking Order Theory, and Trade-Off Theory